Breast cancer patients' experiences of adherence and persistence to oral endocrine therapy: A qualitative evidence synthesis. (February 2020) - Clancy, Caroline; Lynch, Johanna; OConnor, Pamela; Dowling, Maura
Abstract: Purpose: Adjuvant endocrine therapy (AET) significantly reduces the risk of breast cancer recurrence and mortality in women with hormone receptor (HR+) breast cancer. Despite the documented survival benefits with AET, non-adherence and non-persistence remains a significant problem. This systematic review of qualitative research aimed to synthesise breast cancer patients' experiences of adherence and persistence to oral endocrine therapy. Methods: The ENTREQ guidelines were followed. A systematic search strategy was performed across eleven electronic databases (Embase, Cinahl, Pubmed, Psychinfo, Proquest, Lenus, Scopus, Web of Science, Rian.ie, EThOS e-theses online, DART Europe). Thomas and Harden's three-stage approach to thematic analysis was undertaken on the findings of all included studies. Confidence in the findings were reviewed using GRADE-CERQual. Results: Twenty-four qualitative studies were included in the synthesis. Three analytic themes were identified (We don't have an option; the side effects are worse than the disease; help us with information and support). Adherence was often driven by women feeling they had no option and a fear of cancer recurrence. Persistence was helped with support and information. Non-adherence and non-persistence were associated with debilitating side effects, inadequate information and lack of support. Conclusions: Adherence and persistence to AET was often suboptimal among breast cancer patients. Women commonly felt isolated and neglected as a result of insufficient information and support from healthcare professionals. If women are to persist with AET, primary care providers should be aware of the facilitators and barriers to adherence, and they should be knowledgeable in symptom management strategies. Highlights: The presence and severity of the side effects contributes to women's adherence and persistence with oral endocrine therapy. Women prescribed oral endocrine therapy report insufficient information and support from healthcare professionals. Primary care providers should be aware of the facilitators and barriers to adherence, and they should be knowledgeable in symptom management strategies.